HUBUNGAN HUKUM DAN MASYARAKAT - Royan Hanapi; Muhammad Aini (PT. Hasba Edukasi Mandiri, 2025)
Because law regulates human behavior, the existence of law in society is very important because of its function. Law is inseparable from society, and vice versa. In addition to acting passively, law actively monitors every individual action and continues to try to change society. To reduce conflict and problems, the laws that apply in society basically come from society itself. So that the law does not conflict with the values of society, the law must always consider juridical, philosophical, and sociological. Society makes laws to create peace, tranquility, and order and provide legal certainty. If the law can function in society, the purpose of law can be felt comprehensively. Therefore, the relationship between law and society is very important. A country without If there is no law, there will be chaos and arbitrary action, likewise if there is no society, the law has no meaning at all.